Analysis of Overvoltages Resulting from Atmospheric Discharges for Frequency-Dependent Soils - Leon Colqui, Jaimis Sajid (2020)
This paper presents a comparative analysis of the electrode impedance for a vertical rod buried in a homogeneous ground where the soil electrical parameters (resistivity and permittivity) are frequency-dependent in relation to the impedances obtained with frequency-constant parameters. In this study, it is taken into account that vertical rod can be seen as a short transmission line whose electrical parameters (resistance, inductance, capacitance and conductance) are distributed along its length. Thus, the rod impedance is computed as being the harmonic impedance of the transmission line as a function of frequency. Once the rod impedances are obtained, and using the Vector Fitting technique, equivalent electrical circuits are obtained directly in time domain. The advantage of this type of representation is that equivalent circuit can be easily incorporated into EMTP-type programs for the electromagnetic transient analysis. In this model, the grounding potential rise (GPR) generated due to a lightning stroke at the rod can be calculated. Additionally, an impulsive current source, representing a lightning stroke, is injected at the top of a transmission tower whose the grounding system is composed by a vertical rod, and the transient voltages at the cross-arms and tower base are calculated. The results show that the voltages are significantly modified by the presence of the soil with frequency-dependent parameters, especially their voltage peaks, and that an accurate analysis of the transient in power systems must take this phenomenon into account.